PENGARUH PENYULUHAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN TENTANG MENSTRUASI PADA SISWI KELAS IV, V DAN VI DI SD ISLAM TERPADU NURUL ILMI JAMBI - Adek Putri; Sari, Putri Irwanti; Mulyani, Sri (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2022)
Pre-menarche will begin when young women experience puberty, which involves physical, psychological, and cognitive changes, lasting for most of the second decade of life. Menstruation can be a frightening experience if there is a lack of understanding or knowledge about menstruation. Objective : The research was conducted to determine the effect of health education on the level of knowledge about menstruation in grades IV, V and VI students at SD Islam Terpadu Nurul 'Ilmi Jambi. Methods : This research is a pre-experimental that aims to determine the effect that arises as a result of treatment or intervention on a variable. The research design used was one group pre test post test design. The population in the study amounted to 260 students with a total sample of 80 respondents. Results : Most of the respondents before being given counseling (pre-test) had less knowledge as many as 37 people (46.3%), while after being given counseling (post-test) their knowledge increased by 75 people (93.8%). With the statistical test results of the paired sample test, significant results were obtained, namely Ï-value = 0.000. Conclusion : There is an influence of health education on the level of knowledge about menstruation in grades IV, V and VI students at SD Islam Terpadu Nurul 'Ilmi Jambi. Keywords: Menstruation, Knowledge, Health Education, Adolescents